"Kameradschaftsabend". F.l.t.r. Frl. Pütz, Pg. Rudolph, Pg. Rosenfelder, the two persons at the right are unknown
"Kameradschaftsabend". F.l.t.r. Frl. Pütz, Pg. Rudolph, Pg. Rosenfelder, the two persons at the right are unknown.